Acetaminophen, a new tool for the refinement of the experimental infection of toxoplasmosis in mice - Nathalie Moiré; Axel Cauty; Christelle Rossignol; Corinne Beaugé; Laetitia Mérat; Emilie Lortscher; Françoise Debierre-Grockiego; Isabelle Dimier-Poisson; Mickaël Riou (Scientific Reports)
Abstract In recent years, animal welfare gained increasing importance in society and especially in scientific research. It has become necessary to refine the experimental procedures as much as possible in infectiology as in our reference model, toxoplasmosis, in accordance with the 3Rs rule and various ethical concerns. Thus, the establishment of a treatment using analgesics would provide relief to animals acutely infected with Toxoplasma gondii. However, the use of analgesics should in no way alter the pathophysiology of the disease and the host immune response, so as not to interfere with the initial scientific study. Little is currently known about the use of acetaminophen (APAP) in an infectious model. In the present work, we studied the impact of APAP at a reference dose of 30 mg/kg/day in a mouse model of acute toxoplasmosis. Zoonotic, telemetric, behavioral, histological and immune parameters were analyzed to better characterize the consequences of treatment with APAP either by gavage or by self-medication in Gel Water. APAP administered by gavage did not induce cellular or tissue toxicity or alter the physiological development of the mice. In addition, the nature of Gel Water itself, independent of APAP, had an effect on the immune response. APAP improved overall well-being and slowed the onset of clinical signs without altering the physiopathology or the immune responses induced by T. gondii. These first results in mice confirmed our initial hypothesis that APAP appears to be a pharmacological tool to refine and improve animal welfare during the acute phase of toxoplasmosis. Therefore, our project has highlighted the combination of specific markers to contribute to animal welfare in mice. In the long term, the use of APAP could be extended to other infectious models with other target animal species.